Scanning electron microscope energy dispersive X-Ray, chemical, organoleptic, and microbiological quality of banana peel (Musa paradisiaca L.) at different fermentation durations (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: This research aims to examine the effect of different fermentation times on the results of scanning electron microscope energy dispersive X-ray (SEM-EDX), chemical, organoleptic, and microbiological quality of banana peel. Materials and Methods: The design in this study used a completely randomized design (four treatments and four replications). The treatments in this study were different durations of fermentation of banana peels; T0 = no fermentation; T1 = 6 days; T2 = 12 days; and T3 = 18 days. The research parameters were chemical, organoleptic, microbiological quality, composition, and SEM-EDX images. Analysis of chemical, organoleptic, and microbiological quality data was done using analysis of variance, followed by Duncan’s multiple range testing at the 5% significance level, while the elemental composition and SEM-EDX images were analyzed descriptively. Results: The results of the study showed that the length of fermentation had a significant effect (p < 0.05) on moisture content, ash, crude fiber, nitrogen-free extract, and all organoleptic quality variables of banana peels. Different fermentation durations had no effect (p > 0.05) on crude protein, ether extract, metabolic energy, total lactic acid bacteria, total bacteria, Gram positive or negative bacteria, and total fungi on banana peels. The analysis showed that the elemental composition of banana peels is C, Na2 O, Cl, K2 O, MgO, SO3, SiO2, and P2 O5. Conclusion: Eighteen days of fermentation improved the chemical quality, organoleptic, microbiological, elemental composition, and SEM-EDX image of fermented banana peel.J. Adv. Vet. Anim. Res., 9(3): 383–395, September 2022http://doi.org/10.5455/javar.2022.i606